Is One Plus One Always Two? Insuring Longevity Risk While Having Multiple Savings Accounts - Hurwitz, Abigail; Sade, Orly (Management Science, 2025)
We investigate the consequences of holding multiple accounts for payout decisions at retirement. Using proprietary data of retirees’ annuitization decisions, we find that small accounts are more likely to be cashed out. We use occupation information as a proxy for wealth to disentangle income from the multiple-accounts effect. We show that individuals with high expected wages are more likely to annuitize overall but less likely to annuitize their small accounts (comparing to individuals with low wages). A laboratory experiment and an online experimental survey (with a large representative sample) suggest that the composition of multiple accounts affects the annuitization rates via the decisions regarding small versus large accounts. This paper was accepted by Camelia Kuhnen, finance. Funding: This work was supported by the Albertson-Waltuch Chair in Business Administration, the Kruger Center at the Hebrew University, the Think Forward Initiative, and the German-Israeli Foundation for Scientific Research and Development and by funding from the Center for Agriculture, Environment and Natural Resource. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.02489 .